PERGULATAN TAK KUNJUNG USAI: Perdebatan Formalisasi Syari’at Islam di Indonesia - Nasrullah Nasrullah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2012)
The article describes difference approach to understand and toimplement syariat of Islam in context live having state. The conservative orfundamentalist comprehend that syariat have to be practiced totally whether in private law in spite of the public included in state based on Islam or religion. On the other side, moderate group has differ perspective that Islam syariat formalization didn’t need formally, moreover they change state principle becomes Islam. But, it can be channeled toward substance values through mechanism process democratization with legislation approach of Islamic law into positive law of legislation.